Disaster response among hospital nurses dispatched to evacuation centers after the Great East Japan Earthquake: a thematic analysis - Chika Yamamoto; Chieri Yamada; Katsuko Onoda; Morihito Takita; Yasuhiro Kotera; Arifumi Hasegawa; Tomoyoshi Oikawa; Masaharu Tsubokura (BMC, 2022)
Abstract Background Disaster relief operations involve a variety of components of healthcare efforts. The post-disaster recovery is a key component of hospital preparedness. This study aimed to investigate the role of hospital nurses in the disaster area and their challenges during the relief efforts after the Great East Japan Earthquake in 2011. Methods Semi-structured interviews were conducted with ten nurses who worked in a general public hospital before the Great East Japan Earthquake and were dispatched to the evacuation centers after the disaster. A qualitative approach with the thematic analysis method was employed. Three research queries (RQs) were prepared before the interview. Results The study participants played administrative roles as city employees in addition to performing nursing services as healthcare providers in evacuation centers. The first RQ on their challenges in evacuation centers gave us four themes: criticism by the evacuees, conflicts between multiple roles, difficulties in performing the first experience, and anxiety in working. The second RQ asking about motivation to accomplish disaster relief efforts raised three themes of carrying out the nursing role, acceptance by evacuees, and strengths of human connections. Two themes of awareness of disaster medicine and professional growth were raised from the third RQ of gains from the experiences in the evacuation centers. Conclusions The hospital nurses in the disaster area performed multiple roles in the relief efforts in the evacuation centers, which developed a psychological burden on them. A sense of competence supported the motivation to accomplish the disaster relief activities and professional growth as a specialist in disaster medicine. A study limitation is missing hospital nurses who resigned during the relief efforts. Further study is warranted to refine the disaster preparedness of hospital operations.